Identification of an attractant for the nine‐banded armadillo, Dasypus novemcinctus - Holly K. Ober; Lucas W. Degroote; Colleen M. Mcdonough; Russell F. Mizell III; Richard W. Mankin (Wildlife Society Bulletin)
Abstract The nine‐banded armadillo (Dasypus novemcinctus) is considered by many to be one of the greatest nuisance wildlife species in the Southeastern United States. Management is difficult because no repellents, toxicants, or fumigants are currently registered for this species; exclusion is laborious because armadillos are adept burrowers; and no effective trapping attractants have been identified. If a suitable lure were discovered, trap capture success could increase and the frequency of nuisance complaints could decrease. We compared the behavioral attractiveness to captive armadillos of 15 commercially available food materials, as well as scents collected from conspecifics, in Florida, USA, 2008–2009. According to 3 distinct behavioral measures, 4 materials consistently elicited the most attraction responses from armadillos: pond worms (Lumbricus terrestris), crickets (Acheta domesticus), red worms (Eisenia fetida), and wigglers (Pheretima hawayanus). Recognizing that all of these materials were live prey, we devised a second series of experiments to evaluate the relative importance of olfactory cues versus auditory–vibrational cues in evoking a response from armadillos. Results suggested auditory–vibrational cues were meaningful. Finally, we measured sound pressure and vibration levels produced by the most preferred and less preferred prey items. Sound and vibrational cues decreased rapidly below background noise levels within 10–30 cm from baits. Because of this, and because the perceptual range of armadillos to the olfactory cues from these baits appears limited, traps baited with any worm or cricket are unlikely to lure armadillos from great distances. Development of an effective baiting system will require further investigation into the possibility of enhancing the ability of stimuli to travel over long distances. © 2011 The Wildlife Society.